Rev Rene completes 15 years: victories and new challenges - Maria de Nazaré de Oliveira Fraga (Universidade Federal do Ceará, 2015)
There are times when we do not know which words to use. They throw themselves on paper, some or many of them without knowing exactly what will result, as a call for help on what they can show. So simple, so flexible, so hard, so complex they are. The request to write an editorial for the Rene Journal gave me the wheel of time. I'm retired of University teaching and research for a decade and a half. I was editor in chief and also section editor in the mental health area of ​​this journal. So I have a lot to remember.